Relations between abundance characteristics and rotation velocity for star-forming MaNGA galaxies - Pilyugin, Leonid S.; Grebel, Eva K.; Zinchenko, Igor A. (Astronomy and astrophysics, 2019)
We derive rotation curves, surface brightness profiles, and oxygen abundance distributions for 147 late-type galaxies using the publicly available spectroscopy obtained by the MaNGA survey. Changes of the central oxygen abundance (O/H)0, the abundance at the optical radius (O/H)R25, and the abundance gradient with rotation velocity Vrot were examined for galaxies with rotation velocities from 90 km s−1 to 350 km s−1. We find that each relation shows a break at . The central (O/H)0 abundance increases with rising Vrot and the slope of the (O/H)0-Vrot relation is steeper for galaxies with.The mean scatter of the central abundances around this relation is 0.053 dex. The relation between the abundance at the optical radius of a galaxy and its rotation velocity is similar; the mean scatter in abundances around this relation is 0.081 dex. The radial abundance gradient expressed in dex/kpc flattens with the increase of the rotation velocity. The slope of the relation is very low for galaxies with. The abundance gradient expressed in dex/R25 is roughly constant for galaxies with, flattens towards, and then again is roughly constant for galaxies with. The change of the gradient expressed in terms of dex/hd (where hd is the disc scale length), in terms of dex/Re, d (where Re, d is the disc effective radius), and in terms of dex/Re, g (where Re, g is the galaxy effective radius) with rotation velocity is similar to that for gradient in dex/R25. The relations between abundance characteristics and other basic parameters (stellar mass, luminosity, and radius) are also considered.
Gesehen am 14.06.2019